2002
DOI: 10.1002/etc.5620210502
|View full text |Cite
|
Sign up to set email alerts
|

A logical starting point for developing priorities for lizard and snake ecotoxicology: A review of available data

Abstract: Reptiles, specifically lizards and snakes, usually are excluded from environmental contamination studies and ecological risk assessments. This brief summary of available lizard and snake environmental contaminant data is presented to assist in the development of priorities for lizard and snake ecotoxicology. Most contaminant studies were not conducted recently, list animals found dead or dying after pesticide application, report residue concentrations after pesticide exposure, compare contaminant concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 28 publications
0
11
0
2
Order By: Relevance
“…Contaminants are among the six suspected contributors to global reptile declines, but few studies have examined contaminant exposure, maternal transfer, or associated effects in this class of vertebrates [10,11]. Among reptiles, snakes are especially overlooked, with relatively scant contaminant information available for only six of the 15 families [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contaminants are among the six suspected contributors to global reptile declines, but few studies have examined contaminant exposure, maternal transfer, or associated effects in this class of vertebrates [10,11]. Among reptiles, snakes are especially overlooked, with relatively scant contaminant information available for only six of the 15 families [11].…”
Section: Introductionmentioning
confidence: 99%
“…Among reptiles, snakes are especially overlooked, with relatively scant contaminant information available for only six of the 15 families [11]. Snakes feed at high trophic levels and exhibit several ecological and lifehistory traits that increase their susceptibility to bioaccumulation of Hg and other contaminants [12].…”
Section: Introductionmentioning
confidence: 99%
“…Because of declining populations and the discovery of malformations in amphibians and reptiles, they have received much attention from the general public and biologists in the past decade (19). Numerous studies have indicated dramatic reductions in amphibian populations worldwide, with explanations such as climatic change; parasitic, bacterial, or viral infections; and increased predation (20).…”
Section: Congress Passed Thementioning
confidence: 99%
“…Despite recognition that chemical contaminants can and do impact reptiles, the taxon remains understudied in ecotoxicology [2], [3] despite several calls for more research [4], [5]. One of the consequences of a lack of ecotoxicity and exposure data is that ecological risk assessments (ERA) on a reptilian species will have considerable uncertainty reducing the utility of assessment results for sound management decision-making.…”
Section: Introductionmentioning
confidence: 99%